2000
DOI: 10.1253/jcj.64.130
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Aortic Dissection With Transient ST-Segment Elevation due to Functional Left Main Coronary Artery Obstruction

Abstract: A 48-year-old man with a history of hypertension and diabetes mellitus was hospitalized with sudden onset of severe chest pain. He was in cardiogenic shock with a systolic pressure of 60 mm Hg. His electrocardiogram (ECG) showed ST-segment elevation in the precordial leads suggestive of acute anteroseptal myocardial infarction. The ST-segment returned to baseline after the systolic blood pressure rose to 100 mm Hg with the administration of sympathomimetic agents. Aortography and transesophageal echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 8 publications
0
9
1
Order By: Relevance
“…Other reports have shown that ACS in many patients is caused by type-A AAD, 28,29 but in the present study type-B AAD (DeBakey IIIb+r) caused ACS in 3 of patients.…”
Section: Characteristics Of Aad Complicated By Acscontrasting
confidence: 65%
“…Other reports have shown that ACS in many patients is caused by type-A AAD, 28,29 but in the present study type-B AAD (DeBakey IIIb+r) caused ACS in 3 of patients.…”
Section: Characteristics Of Aad Complicated By Acscontrasting
confidence: 65%
“…There are four possible mechanisms for coronary malperfusion in AAD (Ashida, 2000 ;Cambria, 1988;Massetti, 2003 ;Neri, 2001 ;Shapira, 1998,) 1. buldging of the dissected false lumen producing occlusion of the coronary artery orifice ( Distribution of the each mechanism has not been well defined. In our experience Hirata,2010 , among 10 patients in whom actual mechanism of coronary malperfusion was identified during surgery, 5 patients had mechanism 1), 3 patients had mechanism 2) , and 2 patients had mechanism 3).…”
Section: Mechanismsmentioning
confidence: 99%
“…For patients with aortic dissection with coronary malperfusion, some cases revealed aortic dissection truly involving coronary arteries [5,6,8] but others showed no coronary involvement [10,11,12]. Both conditions are uncommon in the literature, but the incidence of the latter is rarer than of the former.…”
Section: Discussionmentioning
confidence: 99%
“…The intimal flap occludes the orifices of the coronary arteries during diastole and leads to severe myocardial ischemia, and even AMI. Shapira and Davidoff [10] reported the first case of aortic dissection with functional obstruction of the left main coronary artery orifice by the intimal flap, and Ashida et al [11] later stated a second case of aortic dissection with transient ST elevation due to a similar mechanism. In our case, the possible mechanism of ST elevation over lead V1–V3 and aVR should also be related to functional obstruction of the left main coronary artery by intimal flap because the left coronary artery was not involved in the dissection and was patent without atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%